The effectiveness of physics e-book that contains balance of scientific literacy aspects in increasing scientific literacy skills : A case study to 32 students in one of public senior high school in Bandung - N Nurdini; I M Sari; I Suyana (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Physics e-book with balance of science literacy aspects on static fluids based on 3D Flip book had been designed and developed. The e-book has been implemented to 32 students to investigate the effectiveness of the e-book. One shot case study design has been chosen as a research design. Scientific literacy skills of the students have been measured after the students were treated in learning aided physics e-book. The research data obtained results test of students’ science literacy skills students related with result of students’ responses on the ebook’s usage. The result showed that the implementation of e-book was effective for use in physics learning, especially in improving of students’ science literacy skills, with an average score of 86.0%. Furthermore, Students provide positive responses on the usage of the developed e-book.